Mitsubishi FX programmable logic controllers : applications and programming - Ridley, J. E. (John E.) (Newnes, 2004)
John Ridley provides comprehensive information on usage, design and programming for the Mitsubishi FX range of programmable logic controllers, in this step-by-step, practical guide. Professional engineers working with Mitsubishi PLCs, as well as students following courses focusing on these devices, will find this book to be an essential resource for this popular PLC family. Numerous worked examples and assignments are included, to reinforce the practical application of these devices, widely used in industry. Fully updated throughout from coverage of the FX PLC to now cover the FxN PLC family from Mitsubishi, John Ridley also focuses on use of the Fx2N - the most powerful and diverse in function of this PLC group. The second edition contains advanced topics along with numerous ladder diagrams and illustrative examples. A hands-on approach to the programming, design and application of FX PLC based systems Programmed using GX Developer software - used worldwide for the whole range of the FX PLC family Covers Ladder Logic tester - the GX developer simulator that enables students and designers to test and debug their programs without a PLC GX Developer demo available on a companion website for the book.